Sexually transmitted infections (STI) and antenatal care (ANC) clinics in Malawi: effective platforms for improving engagement of men at high HIV risk with voluntary medical male circumcision services. Issue 5 (4th January 2021) - Msungama, Wezi; Menego, Geoffrey; Shaba, Frackson; Flowers, Nicole; Habel, Melissa; Bonongwe, Abigail; Banda, Masford; Shire, Steven; Maida, Alice; Auld, Andrew; Phiri, Sam John Peter; Dumbani, Kayira; et al.
Abstract : Introduction: Voluntary medical male circumcision (VMMC), an effective HIV prevention programme for men, is implemented in East and Southern Africa. Approximately 50% of VMMC clients are aged below 15 years. More targeted interventions to reach older men and others at higher short-term HIV risk are needed. Methods: We implemented a quality improvement project testing the effectiveness of an active referral-based VMMC recruitment approach, targeting men attending STI clinics and those escorting partners to antenatal care (ANC) clinics, at Bwaila Hospital in Lilongwe, Malawi. We compared the proportions aged older than 15 years among men who received VMMC following referral from STI and ANC clinics with those among men referred from standard community mobilisation. We also analysed referral cascades to VMMC. Results: In total, 330 clients were circumcised after referral from STI (242) and ANC (88) clinics, as compared with 3839 other clients attributed to standard community mobilisation. All clients from ANC and STI clinics were aged over 15 years, as compared with 69% from standard community mobilisation. STI clinics had a higher conversion rate from counselling to VMMC than ANC (12% vs 9%) and a higher contribution to total circumcisions performed at the VMMC clinic (6% vs 2%). Conclusions: Integrating VMMC recruitment and follow-up in STI and ANC clinics co-located with VMMC services can augment demand creation and targeting of men at risk of HIV, based on age and STI history. This approach can be replicated at least in similar health facilities with ANC and STI services in close proximity to VMMC service delivery.